2018
DOI: 10.14507/epaa.26.3497
|View full text |Cite
|
Sign up to set email alerts
|

Gaps in persistence under open-access and tuition-free public higher education policies

Abstract: The massification of Argentine higher education intensified in the context of open-access and tuition free public university policies. Although Argentina stands out in relation to enrollment in higher education, it faces serious problems in terms of retention and graduation. To study the factors associated with dropout in the higher education system, we use the Permanent Household Survey, or EPH, to measure these phenomena. The EPH is a quarterly national survey that systematically and permanently collects dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 12 publications
(19 reference statements)
0
4
0
7
Order By: Relevance
“…Vale destacar que o uso de modelos preditivos à evasão tem se apresentado na agenda de pesquisadores em todo o mundo. Pesquisas publicadas em periódicos de renome apresentam resultados acerca de modelos preditivos desenvolvidos, fazendo uso de diferentes procedimentos estatísticos (Adrogue & García de Fanelli, 2018;Amaral, 2016;Assis, 2017;Continiet al, 2018;Fonseca, 2018;Rovaris Neto, 2002). Alguns modelos foram desenvolvidos para cenários menores, como para diferentes dimensões (curso, IES e área de estudo) (Assis, 2017) e diferentes momentos do aluno no curso (Fonseca, 2018).…”
Section: Deserción O Permanecia? Modelos Predictivos Para La Gestión unclassified
See 2 more Smart Citations
“…Vale destacar que o uso de modelos preditivos à evasão tem se apresentado na agenda de pesquisadores em todo o mundo. Pesquisas publicadas em periódicos de renome apresentam resultados acerca de modelos preditivos desenvolvidos, fazendo uso de diferentes procedimentos estatísticos (Adrogue & García de Fanelli, 2018;Amaral, 2016;Assis, 2017;Continiet al, 2018;Fonseca, 2018;Rovaris Neto, 2002). Alguns modelos foram desenvolvidos para cenários menores, como para diferentes dimensões (curso, IES e área de estudo) (Assis, 2017) e diferentes momentos do aluno no curso (Fonseca, 2018).…”
Section: Deserción O Permanecia? Modelos Predictivos Para La Gestión unclassified
“…Alguns modelos foram desenvolvidos para cenários menores, como para diferentes dimensões (curso, IES e área de estudo) (Assis, 2017) e diferentes momentos do aluno no curso (Fonseca, 2018). Outros consideraram não somente informações acadêmicas, mas trouxeram enfoque às questões socioeconômicas dos estudantes (Adrogue & García de Fanelli, 2018;Contini et al, 2018). Ainda, identificamos um estudo que verificou a acurácia do modelo em um grupo de controle, alcançando aproximadamente 70% (Amaral, 2016).…”
Section: Deserción O Permanecia? Modelos Predictivos Para La Gestión unclassified
See 1 more Smart Citation
“…On the other hand, parental characteristics are determinants of student attrition. Adrogue and Fanelli (2018) examined predictors of persistence in Argentina. The study showed that students with higher per capita income, students from upper class, and students whose parents were higher education graduate had lower probability of dropping out.…”
Section: Exosystemmentioning
confidence: 99%
“…En los tres casos, la literatura que indaga sobre el abandono de los estudios de nivel superior da cuenta que este afecta especialmente al primer año de los estudios, a los jóvenes de los estratos de menor ingreso, los varones y los que detentan menor capital cultural en su hogar (Adrogué & García de Fanelli, 2018;Fiori & Ramírez, 2014;Rama, 2016;Santelices et al, 2016).…”
Section: Cuadro 5 Tasa De Completitud De La Educación Superior Para Iunclassified